The Relationship between Moral Quotient and Business Ethics of Students of Rajapark Institute - Therdbhuthadham, Theera; Srisatanon, Pornpana (Rajapark Journal, 2021)
The purposes of this research were: (1) to study the level of the moral quotient of students of Rajapark Institute; (2) to study the level of business ethics of students of Rajapark Institute; (3) to compare the different backgrounds of the level of business ethics of students of Rajapark Institute; and (4) to study the relationship between moral quotient and business ethics of students of Rajapark Institute. The population consisted of undergraduate students at Rajapark Institute. The samples were 333 informants. The research instrument was a questionnaire. The reliability was 0.947. The statistics used to analyze the data were mean, standard deviation, independent sample t-test, one-way ANOVA, and Pearson product-moment correlation. The results of the research were as follows: 1. The level of the moral quotient of students at Rajapark Institute was very high overall. 2. The level of business ethics of students at Rajapark Institute was very high overall. 3. The comparison of the level of business ethics of students of Rajapark Institute classified by gender, family income, and domicile was not statistically significant. Meanwhile, the level of business ethics of students of Rajapark Institute classified by faculty of the study was not statistically significant, except that the ethics towards customers was statistically significant at the 0.05 level. 4. The relationship between the moral quotient and business ethics of students of Rajapark Institute was a low positive correlation (r = .169) at a statistically significant level of 0.01.